Association of APOE (E2, E3 and E4) gene variants and lipid levels in ischemic stroke, its subtypes and hemorrhagic stroke in a South Indian population. (15th August 2016) - Das, Satrupa; Kaul, Subhash; Jyothy, Akka; Munshi, Anjana
Highlights: APOE polymorphism (E2, E3 and E4) in certain genetic models associates with development of hemorrhagic stroke. In ischemic stroke subtypes association was observed with intracranial large artery, cardioembolic and lacunar stroke. Lipid levels of very low density lipoprotein and triglycerides were found to be associated with E2/E4 and E3/E4 genotypes in ischemic stroke. Abstract: In the present study we evaluated the association of APOE (E2/E3/E4) polymorphism with ischemic stroke (n = 620), its subtypes and hemorrhagic stroke (n = 250) in a South Indian population from Telangana. The genotypes were determined using PCR-RFLP while lipid levels were measured using commercially available kits. We found significant difference in the genotypic distribution between hemorrhagic stroke patients and controls for certain genetic models [E2/E2 vs. E2/E4; E3/E3 vs. E2/E3; E3/E3 vs. E2/E4; E4/E4 vs. E2/E3; E4/E4 vs.E2/E4 and E3 vs. E4]. However, no significant difference was observed in genotypic distribution between ischemic stroke patients and controls. On analysing the genotypic distribution between ischemic and hemorrhagic stroke patients, statistically significant difference was observed in specific genetic models [E2/E2 vs. E2/E4; E3/E3 vs. E2/E3; E3/E3 vs. E2/E4; E4/E4 vs. E2/E3 and E4/E4 vs. E2/E4]. In ischemic stroke subtypes analysing for alleles E3 vs. E2 and E3 vs. E4, we found significant association with intracranial large artery (p = 0.01), cardioembolic stroke (p = 0.001 and p = 0.0004) and lacunar stroke (p = 0.02). Analysing the association of various genotypes with different lipid levels significant association was observed for VLDL (P = 0.000) and for triglyceride (P = 0.000) levels with E2/E4 and E3/E4 genotypes in ischemic stroke but not in hemorrhagic stroke. In conclusion, our results suggest that APOE polymorphism does seem to play a role in hemorrhagic stroke and also in the development of specific subtypes of ischemic stroke. Further, in ischemic stroke VLDL and triglycerides levels were found to be significantly associated with E2/E4 and E3/E4 genotypes.